Cytokine gene polymorphisms are not associated with anti-PvDBP, anti-PvAMA-1 or anti-PvMSP-1(19) IgG antibody levels in a malaria-endemic area of the Brazilian Amazon - Furini, Adriana A. C.; Capobianco, Marcela P. [UNESP]; Storti-Melo, Luciane M.; Cunha, Maristela G.; Cassiano, Gustavo C.; Machado, Ricardo Luiz D. [UNESP] (Biomed Central Ltd, 2016)
Background: The immune response against Plasmodium vivax immunogenic epitopes is regulated by pro-and anti-inflammatory cytokines that determine antibody levels and class switching. Cytokine gene polymorphisms may be responsible for changes in the humoral immune response against malaria. The aim of this study was to evaluate whether polymorphisms in the TNFA, IFNG and IL10 genes would alter the levels of anti-PvAMA1, PvDBP and -PvMSP-1(19) IgG antibodies in patients with vivax malaria. Methods: Samples from 90 vivax malaria-infected and 51 uninfected subjects from an endemic area of the Brazilian Amazon were genotyped using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) to identify polymorphisms of the genes TNFA (-1031T > C, -308G > A, -238G > A), IFNG (+874T > A) and IL10 (-819C > T, -592C > A). The levels of total IgG against PvAMA1, PvDBP and -PvMSP-1(19) were determined using an enzyme-linked immunosorbent assay (ELISA). Associations between the polymorphisms and the antibody response were assessed by means of logistic regression models. Results: No significant differences were found in the levels of IgG antibodies against the PvAMA-1, PvDBP or PvMSP-1(19) proteins in relation to the studied polymorphisms. Conclusions: Although no associations were found among the evaluated genotypes and alleles and anti-merozoite IgG class P. vivax antibody levels, this study helps elucidate the immunogenic profile involved in the humoral immune response in malaria.
Keywords: IgG antibody; Plasmodium vivax; TNF; IFNG; IL10